Bats are Not Birds – Different Responses to Human Land‐use on a Tropical Mountain. (4th June 2015) - Helbig‐Bonitz, Maria; Ferger, Stefan W.; Böhning‐Gaese, Katrin; Tschapka, Marco; Howell, Kim; Kalko, Elisabeth K. V.
Abstract Land‐use intensification has consequences for biodiversity and ecosystem functioning, with various taxonomic groups differing widely in their sensitivity. As land‐use intensification alters habitat structure and resource availability, both factors may contribute to explaining differences in animal species diversity. Within the local animal assemblages the flying vertebrates, bats and birds, provide important and partly complementary ecosystem functions. We tested how bats and birds respond to land‐use intensification and compared abundance, species richness, and community composition across a land‐use gradient including forest, traditional agroforests (home garden), coffee plantations and grasslands on Mount Kilimanjaro, Tanzania. Furthermore, we asked how sensitive different habitat and feeding guilds of bats and birds react to land‐use intensification and the associated alterations in vegetation structure and food resource availability. In contrast to our expectations, land‐use intensification had no negative effect on species richness and abundance of all birds and bats. However, some habitat and feeding guilds, in particular forest specialist and frugivorous birds, were highly sensitive to land‐use intensification. Although the habitat guilds of both, birds and bats, depended on a certain degree of vegetation structure, total bat and bird abundance was mediated primarily by the availability of the respective food resources. Even though the highly structured southern slopes of Mount Kilimanjaro are able to maintain diverse bat and bird assemblages, the sensitivity of avian forest specialists against land‐use intensification and the dependence of the bat and bird habitat guilds on a certain vegetation structure demonstrate that conservation plans should place special emphasis on these guilds.